2021
DOI: 10.3390/w13070910
|View full text |Cite
|
Sign up to set email alerts
|

Landfill Pollution Plume Survey in the Moroccan Tadla Using Spontaneous Potential

Abstract: In many parts of the world, the impact of open landfills on soils, biosphere, and groundwater has become a major concern. These landfills frequently generate pollution plumes, the contours of which can be delineated by non-intrusive geophysical measurements, but in arid environments, the high soils resistivity is usually an obstacle, which results in the low number of studies that have been carried out there. In addition, such prospecting using geophysical techniques do not provide information on the intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The similarity of the data in the two profiles and the absence of low depth anomalous zones show the decreasing effect of the contamination plumes on the subsoil and the subsurface environment as one move away from the dump to the North, due to the natural process of attenuation by dilution and dispersion of the plumes in the natural receiving basin. Similar situations have been described in areas around several dumpsites in Africa, Morocco by El Mouine et al [59] and Touzani et al [47], Nigeria by Fatoba et al [60] and Burkina Faso by Barry et al [61]. Zone 1 -Profile 4 (a) from the beginning to 120 m shallow shows zones with anomalous resistivities.…”
Section: Geophysical Studies (Electrical Resistivity)supporting
confidence: 77%
“…The similarity of the data in the two profiles and the absence of low depth anomalous zones show the decreasing effect of the contamination plumes on the subsoil and the subsurface environment as one move away from the dump to the North, due to the natural process of attenuation by dilution and dispersion of the plumes in the natural receiving basin. Similar situations have been described in areas around several dumpsites in Africa, Morocco by El Mouine et al [59] and Touzani et al [47], Nigeria by Fatoba et al [60] and Burkina Faso by Barry et al [61]. Zone 1 -Profile 4 (a) from the beginning to 120 m shallow shows zones with anomalous resistivities.…”
Section: Geophysical Studies (Electrical Resistivity)supporting
confidence: 77%
“…Self-potential measurements along the transects were made every 3 or 4 m. For this short distance, the variogram shows a nugget effect, partly due to the measurement oscillating in a range of less than 2 mV during the reading. In addition, the distance between transects was kept below 150 m. For this value, the variogram shows a half variance of about 230 mV 2 , which is about one third of the value of the sill (~700 mV 2 ) reached for a range of about 450 m. It can be concluded that the spacing is at the limit, but sufficient for interpolation of values between transects [27]. On the correlogram, the correlation coefficient zeroes for a value of the order of 400 m. All these results indicate that the density of measurements allows extrapolation between transects and therefore allows fairly reliable mapping of the spontaneous potential over the prospected area.…”
Section: Reliability Of Data and Mappingmentioning
confidence: 99%
“…Such mapping from boreholes and wells is very random and costly. This difficulty is compounded by the complexity of groundwater flow in space and time, as the extent and direction of a contaminant plume can change over the seasons [2,3]. Predicting the spread of a pollution plume is relatively easy to delineate, monitor and model in the context of aquifers in porous sedimentary environments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this retention also occurs because the disturbed backfill over the interred remains has a higher porosity and permeability than the native soil. This is likely to be true in most cases except perhaps clayey sands if they are watered-in at the time of backfilling thus allowing for repacking of grains and flushing of clays into pore spaces [13]. Other backfill types ultimately settle and/or differential settlement occurs as the interred remains decompose and coffins collapse; some clayey backfill bridge-essentially leaving cavities at depth.…”
Section: Grave Function: Bucket Effectmentioning
confidence: 99%
“…Nitrate and Sulphate had high values showing that the observed analytes in the water sample as seen earlier, could be as a result of migration of these metals. Other parameters showed varying amount (Figs [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]…”
mentioning
confidence: 99%